LEGAL PROTECTION FOR INVESTORS AND BUSINESS ACTORS WHO HAD THOROUGH BANKRUPTCY DUE TO FORCE MAJEURE IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) - Dewi, Gusi Ayu Arya Anindyanari Auliani; Mahendrawati, Ni Luh Made; Styawati, Ni Komang Arini (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
This research examines the legal protection provided to investors and business actors regarding bankruptcy caused by force majeure in micro, small and medium enterprises (MSMEs). Force majeure is a condition beyond control that may lead to the inability to fulfill financial obligations. The primary objective of this research is to examine the existing legal protection mechanisms for investors and MSME businesses in handling bankruptcy situations caused by force majeure. Through a normative law approach and literature study, this research investigates the legal framework governing the responsibilities and protections for investors and MSME businesses against force majeure. The research findings are expected to provide a better comprehension of the legal measures that can be taken to protect the interests of investors and MSME businesses in handling the risk of bankruptcy due to force majeure. Although there are several regulations that provide a framework to protect investors and MSME businesses in bankruptcy situations, implementation and enforcement often causes challenges. Hence, it is significant to have more active endeavors from the government, financial institutions, and other stakeholders to strengthen legal protection for investors and MSME businesses in handling the risk of bankruptcy due to force majeure.